Alberta Geological Survey Research - Mossop, Grant (Geoscience Canada, 1984)
Summary Geological research and survey work by the Alberta Geological Survey is concentrated in three main areas — energy resources, mineral resources and environmental geology. The collective results of current investigations reveal some exciting new perspectives on Alberta's geology, particularly with regard to the faciès and depositional environments of the oil sands, petroleum and coal-bearing strata of the plains, the industrial mineral potential of the province, and the region's Quaternary stratigraphy and glacial history.